2009
DOI: 10.1007/s10535-009-0053-8
|View full text |Cite
|
Sign up to set email alerts
|

Dark and light green tissues of tobacco leaves systemically infected with tobacco mosaic virus

Abstract: There are significant changes in the structure of the upper tobacco (Nicotiana tabacum L.) leaves systemically infected with tobacco mosaic virus (TMV) especially in the light green tissue (LGT). Dark green areas (DGI) had intermediate status between healthy tissue and LGT. DGI contained significantly less infectious TMV and viral antigen than the LGT. The DGI, LGT and healthy tissues did not differ in the permeability of cell membranes and in the set of acidic pathogenesis-related (PR) proteins but the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…An analysis of DEGs showed that the genes encoding CMV RNA-directed RNA polymerase 2a, CMV replication protein 1a and CMV movement protein were significantly up-regulated in LGTs vs. DGIs and LGTs vs. CK. This finding was somewhat consistent with the previous suggestion that DGIs were free of viral RNAs and proteins [ 7 , 9 , 13 , 16 ]. Previous studies reported that genes related to photosynthesis and pigment metabolism were suppressed by virus infection [ 55 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…An analysis of DEGs showed that the genes encoding CMV RNA-directed RNA polymerase 2a, CMV replication protein 1a and CMV movement protein were significantly up-regulated in LGTs vs. DGIs and LGTs vs. CK. This finding was somewhat consistent with the previous suggestion that DGIs were free of viral RNAs and proteins [ 7 , 9 , 13 , 16 ]. Previous studies reported that genes related to photosynthesis and pigment metabolism were suppressed by virus infection [ 55 ].…”
Section: Discussionsupporting
confidence: 93%
“…DGIs, which are somewhat of a mystery in plants, have attracted the attention of many researchers [ 4 ]. Therefore, extensive literature is available concerning the comparison of DGIs and LGTs [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhuravlev et al (1983) standardized tobacco protoplast sources in studies on tobacco mosaic virus to LPI 1–3 leaves from PI 16–18 plants. The PI and LPI has been used to standardize experimental and control plants inoculated with tobacco mosaic virus (Burundukova et al, 2009) as well as follow the progression of viral diseases in intact (Derrick et al, 1997) and grafted (Malinovskii et al, 1994) plants, and tissue and cell cultures obtained from inoculated plants (Malinovskii et al, 1993).…”
Section: Application Of the Plastochron Indexmentioning
confidence: 99%